Transformative Fiqh and Health Technology: An Islamic Ethical Study of The Use of Artificial Intelligence in Medical Practice - Mashuri, Mashuri (IAIN PONOROGO, 2025)
This study aimed to analyze the use of Artificial Intelligence (AI) in medical practice through a transformative fiqh and Islamic ethics approach. Based on the rapid development of health technology, the role of AI in diagnosis, treatment, and medical decision-making continues to expand, raising issues related to patient privacy, professional responsibility, and the risk of algorithmic discrimination. Therefore, an ethical framework rooted in the fundamental values of Islamic law (maqashid syari’ah) within the context of transformative fiqh becomes necessary. This study uses a qualitative method with a normative-philosophical approach, supported by selected literature sources tested for accuracy and validity, and analyzed through concept identification, issue mapping, comparison with maqashid, and legal synthesis. The study finds that the use of AI is ethically acceptable when placed within the framework of mashlahah, accompanied by professional oversight, and regulated through justice-based policies. Transformative fiqh also highlights the need to balance technological benefits with potential risks, including protecting patient rights, ensuring fairness in service, and preserving spiritual values in treatment. Ultimately, AI in medical practice is viewed not only as a technological tool but also as a means to actualize the core values of Islamic law in contemporary contexts. This study contributes by offering a relevant Islamic ethical framework for the development of health technology in the digital era through a transformative fiqh approach.